Differential emergence of cellular mechanisms mediating habituation and sensitization in the developing Aplysia nervous system - Rayport, SG (J Neurosci, 1984)
The development of the cellular substrates underlying habituation and sensitization, two simple forms of learning, was examined at a polysynaptic sensory-to-motor connection in the neural circuit mediating defensive mucus release in the marine mollusc, Aplysia californica. Animals were studied throughout juvenile life, stages 9 (40 days of development) to 12 (95 days), and into adulthood, stage 13 (120 days), starting just after metamorphosis when mucus release first becomes evident. Homosynaptic depression, which mediates habituation, was already present in its adult form in stage 9. Heterosynaptic facilitation, which mediates sensitization, appeared in stage 10 and reached maturity during stages 11 and 12. Thus, the development of synaptic plasticity in this circuit occurs in discrete phases in which the gradual emergence of heterosynaptic facilitation occurs only after homosynaptic depression is well established.